Jagruti : Suvendu Sekhar Mahapatra Electronics and Telecommunication to Solid Waste Management - Kar, Brajaballav; Tripathy, Sugato (AMC Indian Journal of Entrepreneurship, 2020)
How an electronics and telecommunication engineer became an entrepreneur and managed the municipal solid waste (MSW) system of a smart city ? MSW management is a labour intensive job which involves ridiculous work hours, and is subjected to immense pressures from citizens and many other stakeholders. The dimensions involved are varied and unique - managing illiterate or semi-literate workforce, scheduling different zones to ensure the completion of work in time, effective monitoring of the work, operating within the cost constraints, and managing the cumbersome bureaucratic process of the government. How many novice entrepreneurs would like to get into such a sector? This case study presents the sequence of events, dynamics, and challenges of an entrepreneur in this sector. It also briefly discusses various aspects of managing MSW. The case study supporting resources are given to facilitate case discussion with the participants.